MICRO-MATERIAL HANDLING, EMPLOYING E-BEAM COATINGS OF COPPER AND SILVER - Matope, S.; Van der Merwe, A.F.; Rabinovich, Y.I. (The South African Journal of Industrial Engineering, 2011)
ENGLISH ABSTRACT: Van der Waals forces and other adhesive forces impose great challenges on micro-material handling. Mechanical grippers fail to release micro-parts reliably because of them. This paper explores how the problematic Van der Waals forces may be used for micro-material handling purposes using surface roughnesses generated by e-beam coatings of copper and silver on silicon. An atomic force microscope, model Asylum MFP 3 D-Bio with version 6.22A software, was used to measure the forces exerted by the surfaces. A silver coating of 1.41 nm rms surface roughness value is found to exert the highest Van der Waals force, followed by a copper coating of 2.72 nm rms; a copper coating of 217 nm rms exerts the least force. This implies that, in a reliable micro-material handling system, these coatings are suitable for the interactive surfaces of the placement position, micro-gripper, and the pick-up position respectively. AFRIKAANSE OPSOMMING: Van der Waalskragte en ander bindingskragte hou steeds groot uitdagings in vir mikromateriaalhantering. As gevolg van hierdie bindingskragte stel meganiese gryptoerusting nie die mikro-partikels vry nie. Hierdie artikel ondersoek hoe die Van der Waalskragte gebruik kan word vir die mikro-materiaalhanteringsproses deur die gebruik van oppervlakgrofheid gegenereer deur